2018
DOI: 10.1183/13993003.01419-2017
|View full text |Cite
|
Sign up to set email alerts
|

Palatal prolapse as a signature of expiratory flow limitation and inspiratory palatal collapse in patients with obstructive sleep apnoea

Abstract: Objectives In some individuals with obstructive sleep apnea (OSA), the palate prolapses into the velopharynx during expiration, limiting airflow through the nose or shunting it out the mouth. We hypothesized that this phenomenon causes expiratory flow limitation (EFL) and is associated with inspiratory “isolated” palatal collapse. We also provide a robust non-invasive means to identify this mechanism of obstruction. Methods Using natural sleep endoscopy, 1211 breaths from 22 OSA patients were scored as havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…; Azarbarzin et al . ). Similalrly, pharyngeal collapsibility can now be estimated from routine diagnostic polysomnography (Azarbarzin et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Azarbarzin et al . ). Similalrly, pharyngeal collapsibility can now be estimated from routine diagnostic polysomnography (Azarbarzin et al .…”
Section: Discussionmentioning
confidence: 97%
“…The velum and the uvula can also prolapse into the velopharynx during expiration, causing air to escape through the mouth. 23 This palatal prolapse during DISE has been shown to limit expiratory flow. Researchers concluded that the phenomenon of expiratory palatal prolapse could be caused by an elongated palate, a swollen uvula, or excess soft palatal tissue.…”
Section: Velummentioning
confidence: 99%
“…Researchers concluded that the phenomenon of expiratory palatal prolapse could be caused by an elongated palate, a swollen uvula, or excess soft palatal tissue. 23 This increase in expiratory pressure and fluttering of tissue could lead to oral exhalation. Additionally, it was also hypothesized that this mechanism could lead patients to become mouthbreathers, as it has been shown that children who mouthbreathe are at a higher risk of tongue base collapse.…”
Section: Velummentioning
confidence: 99%
“…This suggests that the airway is most prone to collapse towards end expiration. However, recent studies that have investigated inspiratory (Genta et al 2017) and expiratory flow (Azarbarzin et al 2018) limitation have highlighted the propensity for inspiratory collapse in many individuals. These studies have also highlighted the link between the structures that contribute to pharyngeal collapse and the pattern and timing of airflow limitation.…”
Section: Introductionmentioning
confidence: 99%